Correlation of the renal index calculated by anterior and posterior image by posterior image only - Ciftci, I; Balci, TA (Springer, 2004)
[Abstract Not Available]
17th Annual Congress of the European-Association-of-Nuclear-Medicine -- SEP 04-08, 2004 -- Helsinki, FINLAND